Positive transformational leadership: case study of an Indian public sector bank. Issue 1 (7th April 2015) - Bhandarker, Asha; Rai, Snigdha
Abstract : Purpose: – The purpose of this paper is to explore the leadership style of Chairman and Managing Director (CMD) and perceived organizational climate of an Indian public sector bank. Design/methodology/approach: – For the present study data were collected using mixed-method approach including both semi-structured interview and inventories. Sample included the top, middle, and senior-middle level officials of the bank. Findings: – Data were analyzed using content analysis and descriptive statistics. Findings indicated that: the perceived leadership style of CMD is a combination of transformational leadership and positive leadership; there is a positive organizational climate prevalent in the bank; and positive transformational leadership style of CMD has played a considerable role in the development of positive organizational climate in the bank. Originality/value: – Present study provides valuable insights regarding contemporary leadership style in an Indian organization which is the combination of both positive and transformational leadership style and its contribution to building positive organizational climate.